NERVOUS SYSTEM DAMAGE IN HIV INFECTION AND AIDS - Jasur Mukhammadi Oʻgʻli, Egamberdiev; Umid Arzikulovich, Qodirov; Sokhiba Ziyadulloyevna, Khakimova (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to explore the neurological complications of HIV infection, specifically the impact of HIV on the nervous system, including the role of the glycoprotein gp120 in neuronal damage. Methods: A review of HIV-related neurological impairments, focusing on the mechanisms of viral infection and the consequences on glial and neuronal cells, was conducted. The study examines the direct and indirect damage caused by the virus and associated factors such as opportunistic infections, tumors, and the effects of antiretroviral drugs. Results: : The study finds that HIV infection affects approximately one in every hundred cells in brain tissue, significantly impacting glial cells, neurons, and other cells possessing the CD4 receptor. HIV damages these cells through direct infection and by the destructive effects of the gp120 glycoprotein, which leads to membrane lysis and neurotoxic consequences such as an increased Ca2+ ion load in astrocytes. Novelty: This research highlights the critical role of gp120 in the pathogenesis of HIV-induced neuronal damage, specifically its interference with neuroleukin and the glutamate retention mechanisms in astrocytes, which are key to understanding HIV-related neurological disorders.